2021
DOI: 10.1021/acs.jpcc.1c00987
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Deuterium Molecular Escape from Clathrate Hydrates: “Leaky” Microsecond-Molecular-Dynamics Predictions

Abstract: It is predicted herewith that the leakage of both hydrogen (H 2 ) and deuterium (D 2 ) from sII clathrate hydrates, borne of guest chemical-potential equalization driving enhanced nonequilibrium intercage hopping, should be observable experimentally. To this end, we have designed simulations to realize and study this process by microsecond molecular dynamics within the temperature range of 150–180 K—for which the hydrate lattice was found to be stable. In this purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…47 Additionally, a similar behaviour has been observed for other small guests, such as hydrogen. [74][75][76][77] Therefore, in order to shed more light on this matter, three different He-filled sII structures will be investigated in this work: He (1/1) @sII, He (1/4) @sII and He (2/4) @sII. The empty sII crystal will also be considered in order to check the influence of the He guests on the lattice.…”
Section: Resultsmentioning
confidence: 99%
“…47 Additionally, a similar behaviour has been observed for other small guests, such as hydrogen. [74][75][76][77] Therefore, in order to shed more light on this matter, three different He-filled sII structures will be investigated in this work: He (1/1) @sII, He (1/4) @sII and He (2/4) @sII. The empty sII crystal will also be considered in order to check the influence of the He guests on the lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Based on MD analysis of H2 and D2 molecular scape from the hydrate phase using the same force-field parameters at 150 to 195 K, it was also revealed that the stronger collisions between the cage and guest molecules may increase the likelihood of cage distortion which results in the subsequent escape of D2 molecules. Also, the leakage rates of H2 were observed to be lower than those for D2 [218]. In addition, the in-slab translational order parameters of the CH4 hydrate surface in contact with the gas phase determined that the molecules of water in the adlayers and slab surfaces can be periodically arranged while the internal slabs can remain completely rigid [97].…”
Section: Thermo-physical and Mechanical Properties Of Gas Hydratementioning
confidence: 95%